Neuroprotective Mechanisms of Glucagon-Like Peptide-1-Based Therapies in Ischemic Stroke: An Update Based on Preclinical Research - Yang, Xiaoyan; Qiang, Qiang; Li, Nan; Feng, Peng; Wei, Wenshi; Hölscher, Christian (Frontiers in Neurology, 2022)
The public and social health burdens of ischemic stroke have been increasing worldwide. Hyperglycemia leads to a greater risk of stroke. This increased risk is commonly seen among patients with diabetes and is in connection with worsened clinical conditions and higher mortality in patients with acute ischemic stroke (AIS). Therapy for stroke focuses mainly on restoring cerebral blood flow (CBF) and ameliorating neurological impairment caused by stroke. Although choices of stroke treatment remain limited, much advance have been achieved in assisting patients in recovering from ischemic stroke, along with progress of recanalization therapy through pharmacological and mechanical thrombolysis. However, it is still necessary to develop neuroprotective therapies for AIS to protect the brain against injury before and during reperfusion, prolong the time window for intervention, and consequently improve neurological prognosis. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are broadly regarded as effective drugs in the treatment of type 2 diabetes mellitus (T2DM). Preclinical data on GLP-1 and GLP-1 RAs have displayed an impressive neuroprotective efficacy in stroke, Alzheimer's disease (AD), Parkinson's disease (PD), Amyotrophic lateral sclerosis (ALS), and other neurodegenerative disorders. Based on the preclinical studies in the past decade, we review recent progress in the biological roles of GLP-1 and GLP-1RAS in ischemic stroke. Emphasis will be placed on their neuroprotective effects in experimental models of cerebral ischemia stroke at cellular and molecular levels.